Factors shaping on-farm genetic resources of sorghum [Sorghum bicolor (L.) Moench] in the centre of diversity, Ethiopia - Mekbib, Firew; Bjornstad, A.; Sperling, L.; Synnevag, G (2009)
Ethiopia is cited as one of the centres of sorghum diversity. In order to assess the on-farm genetic resources management of sorghum various research methodologies were employed. These were focus group interviews with 360 farmers, key informant interviews with 60 farmers and development agents and semi-structured interviews with 250 farmers. Besides, diversity fair was done with over 1200 farmers. For quantifying on-farm diversity, direct on-farm monitoring and participation with 120 farmers were made. Quantification of varietal diversity per farm was counted by a participatory zigzag sampling in the diagonal direction of the plot with the farmer and all encountered varieties were counted. Soil samples were taken from 120 farms and were subjected to analyses of soil pH, P, available nitrogen, organic matter and exchangeable potassium. Altitude and other related climatic data were collected. The number of varieties conserved by farmers ranged from one to twenty per farm and this is affected by socio-economic and biophysical factors. The mean numbers of 8.3 and 6.3 varieties were grown by Oromo and Amhara farmers respectively. The minimum and maximum range did not vary for both ethnic groups. There was no significant difference in the number of varieties held by various wealth groups. With respect to farm size as explained by the quadratic model, it significantly accounted and predicted for the variation in the number of varieties. The role of soil pH, P, available nitrogen, organic matter, and exchangeable potassium on-farm genetic diversity is described. P was a positive limiting factor for varietal diversity. As to the effect of crop ecology, there were higher number of varieties in the intermediate altitudes than in the lowland and highland. Both the quadratic and linear equation expressed that distance from the house and town and showed non-significant relationship to the number of varieties planted per farm. Varietal mixture is one of the strategies used by the farmers for improved on-farm genetic diversity management. Farmers' underlying principles for conserving genetic diversity is described. Three models developed, namely; Bioecogeographic genetic diversity model, Farmer induced genetic diversity model and Farmer-cum-bioecogeographic genetic diversity model are explaining the processes shaping on-farm genetic diversity of sorghum in Ethiopia.